Assessing LED from below in Mexican municipalities: A quantitative analysis for the period 1990-2005 - Eduardo Ivan Palavicini Corona (European Regional Science Association (ERSA), 2010)
Different levels of government, multilateral organisations such as the World Bank (WB), and a great number of non-governmental organisations around the globe state either explicitly or implicitly their intentions to improve the development of places. Their main goal is to help societies to achieve higher standards in economic, educational, health and social security aspects, among others. To do this, they put emphasis on particular issues and, as a consequence, many adjectives to the word development have become common in the public policy literature. Thereby, combined words like human development, economic development, sustainable development and social development are familiar among practitioners and experts working to improve the well-being of people in diverse parts of the world. In addition, since 1990 scholars and multilateral organisations such as the Organisation for Economic Cooperation and Development (OECD) have recommended a local (i.e. the lowest sub-national level) response to the development challenges and opportunities originated by the globalisation of the world economy. In this context, the impact of bottom-up strategies towards local economic development has not been sufficiently assessed for both developed and developing countries. This paper presents a first approximation towards assessing the impact of such strategies in Mexican municipalities by proposing a simple model linking them to measures of human and social well-being such as the components of the human development index (HDI) calculated since 1990 by the United Nations Development Programme.
Keywords: 330